Determinan Sikap Permisif Masyarakat Terhadap tambang Ilegal Kelurahan Sambutan, Kota Samarinda - Rahmadania, Annisa; Gunawan, I Ketut (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to identify the determinants of community permissiveness toward illegal mining in Sambutan Sub‑district, Samarinda City. Using a quantitative, associative design, the research evaluates relationships among multiple variables. Fieldwork was conducted in neighbourhood units (RT) 18 and 20, with a sample of 62 respondents. Data were collected through questionnaires and documentation, then analysed with Product‑Moment correlation, partial correlation, multiple linear regression, prediction‑accuracy tests, and the coefficient of determination. The results indicate that educational level, corporate strategies, and the involvement of local actors exert positive and significant effects on community permissiveness. Together, these three variables account for 86.4 per cent of the variance in permissive attitudes, while the remaining 13.6 per cent is attributable to other factors not examined in this study.